Centrosomal protein of 192 kDa (Cep192) promotes centrosome-driven spindle assembly by engaging in organelle-specific Aurora A activation - Joukov, Vladimir (National Academy of Sciences, 2010)
Centrosomes are primary microtubule (MT)-organizing centers (MTOCs). During mitosis, they dramatically increase their size and MT-nucleating activity and participate in spindle assembly from spindle poles. These events require the serine/threonine kinase, Aurora A (AurA), and the centrosomal protein of 192 kDa (Cep192)/spindle defective 2 (Spd-2), but the underlying mechanism remains unclear. We have found that Cep192, unlike targeting protein for Xklp2 (TPX2), a known MT-localizing AurA activator, is an AurA cofactor in centrosome-driven spindle assembly. Cep192, through a direct interaction, targets AurA to mitotic centrosomes where the locally accumulating AurA forms homodimers or oligomers. The dimerization of endogenous AurA, in the presence of bound Cep192, triggers potent kinase activation that, in turn, drives MT assembly. Depletion of Cep192 or specific interference with AurA-Cep192 binding did not prevent AurA oligomerization on MTs but abrogated AurA recruitment to centrosomes and its activation by either sperm nuclei or anti-AurA antibody (αAurA)-induced dimerization. In these settings, MT assembly by both centrosomes and αAurA-coated beads was also abolished or severely compromised. Hence, Cep192 activates AurA by a mechanism different from that previously described for TPX2. The Cep192-mediated mechanism maximizes AurA activity at centrosomes and appears essential for the function of these organelles as MTOCs.